Embedding equity, diversity and inclusion processes within clinical trials and health and social care research - Robina Coker; Marta Boffito; Helen Jones; Stephen Cole; Amrinder Sayan; Laura Mitchell; Gayathri Perera; Simon Lewis; Keerti Gedela; Christiana Dinah; Richard Wong; Stuart Blackburn; et al. (BMJ Open)
The lack of diverse and inclusive clinical research populations fuels health inequalities in the UK, and there is an urgent need to reverse this. This communication provides a practical framework for positive action to integrate equity, diversity and inclusion (EDI) processes into clinical research design, protocols and implementation and to establish accountable clinical research systems that are trustworthy to the public and accessible to diverse communities.This framework is a consensus-based guide developed by the Equality, Diversity and Inclusion working group of the National Institute for Health and Care Research’s (NIHR’s) Clinical Research Network in North West London. This work involved analysing challenges to integrating EDI within the clinical research process, such as clinical trial protocols as directed by industry sponsors and National Health Service investigator teams. It aligns with the UK government’s clinical research strategy and NIHR’s INCLUDE project.It advises an interconnected approach to embedding EDI throughout the clinical research lifecycle. By following this framework, we aspire to guide clinical research towards a more equitable, inclusive and representative model that better serves the needs of all populations.